Le lettere di Quintino Sella (1827-1884) a Giovanni Capellini (1833-1922) nella Biblioteca dell’Archiginnasio a Bologna (1861-1884) - The Correspondence by Q. Sella to (1827-1884) to G. Capellini (1833-1922) at the Archiginnasio Library in Bologna - Gian Battista Vai (Rivista di Storia dell'Università di Torino)
This is a business correspondence mainly devoted to two major items of scientific policy and organization. The one is concerned with the Geological Mapping of Italy at large scale as a new unite State, and the other with the updating of the ancient and glorious Accademia dei Lincei in Rome 1603. The second was fulfilled in the 1870s by Sella also with the help of Capellini well acquainted at the level of scientific organizers worldwide. The first, instead, failed dramatically for both inadequate investments and basic management disagreements between the pre-existing Mining Engineers Corp of the Savoia Kingdom and the geologist community assembled following the dissolution of the formers small Italian States. Sella and Capellini were good friends through their life, but enjoyed antithetic characters, thus benefiting almost complete integration which glimpse also from the correspondence.